The Moderating Role of Self-Regulation in the Relationship Between Social Media Addiction and Academic Procrastination - Haidari, Ali Reza; Hassanzadah, Mohammad Mahdi; Hassani, Mahdi (Journal of Social Sciences and Humanities, 2026)
Social media addiction is positively associated with academic procrastination among university students. Nevertheless, the influence of self-regulation within this relationship remains underexplored in the context of Afghanistan. This study examined the association between social media addiction and academic procrastination, as well as the moderating effect of self-regulation, among university students. A cross-sectional, descriptive-correlational design was utilized with a sample of 215 students from the Faculty of Education at Bamyan University. Data were collected using standardized questionnaires and analyzed through Pearson correlation and hierarchical moderated regression analysis in SPSS-27. Before calculating the interaction term, the predictor and moderator variables were mean-centered. The results showed a significant positive link between social media addiction and academic procrastination (r = 0.545, p < 0.001). Self-regulation had significant negative relationships with both academic procrastination (r = -0.239, p < 0.001) and social media addiction (r = -0.228, p < 0.001). The overall regression model was significant (R² = 0.312, F = 38.178, p < 0.001). The interaction between social media addiction and self-regulation was also significant and negative (β = -0.230, p < 0.05). This means that self-regulation reduces the positive link between social media addiction and academic procrastination. In other words, when self-regulation is higher, the connection between social media addiction and academic procrastination is weaker, leading to less academic procrastination.